Caracterização fenotípica de células de sertoli de ratos (Rattus novergicus) localizadas na região de transição entre os túbulos seminíferos e a Rete Testis - Andre Felipe de Figueiredo Almeida (2015)
The region that connects the seminiferous tubules (ST) to the rete testis, known as the transition region (TR) or transitional zone, is an area of the testis that has not yet been well characterized. Therefore, its morphofunctional importance for spermatogenesis and testis function as a whole is not yet completely understood. Particularly, the peculiar characteristics of the TR, such as the presence of morphologically modified Sertoli cells (SC) and the distinct immunomorphological aspects of this region, as well as the surrounding interstitium, motivated us to investigate if those cells are phenotypically different (i.e. express different factors or molecules) from SC located in other ST area. In the present study we have evaluated several important parameters related to the SC proliferation/differentiation and the expression of the monocyte chemoattractant protein 1 receptor (CCR2) along the seminiferous tubules (ST), in the TR, and in the connection between ST and the TR (Cx) in prepubertal and adult Wistar rats. Using immunostaining, the cell proliferation was investigated through Ki67 and BrdU, while p27, GATA4, androgen receptor (AR) expressions were studied in order to evaluate the SC differentiation status. CCR2 expression was assessed in order to evaluate the interaction between the immune cells and SC. Unlike what is established in the literature, in which is considered that SC stop proliferating in vivo at 23 weeks of age in rats, we found Ki67 and BrdU positive SC at 36 and 120 daysold. However those mitotic SC were present only in the TR. Regarding the SC maturation, at both ages and different from the other areas, we observed SC located in the TR that did not express AR or GATA4. Also, in comparison to the Cx and ST, in general a lower AR expression was found in SC located in the TR. Furthermore, in older rats, the SC present in the TR showed a higher CCR2 expression. This elevated CCR2 expression could be involved in the induction of selfantigens tolerance or with cell proliferation, as observed in prostate cancer. Taken together, these findings suggest a distinct behavior/function of SCs located in TR, leading us to hypothesize the presence of transiently amplifying SC subpopulation in this region.